1982
DOI: 10.1111/j.1399-3054.1982.tb02268.x
|View full text |Cite
|
Sign up to set email alerts
|

A precursor of the reserve‐protein, phaseolin, is transiently associated with the endoplasmic reticulum of developing Phaseolus vulgaris cotyledons

Abstract: 1982. A presursor of the reserve-protein, phaseolin, is transiently associated with the endoplasmic reticulum of developing Phaseolus vulgaris cotyledons. -Physio!. Plant. 55: 82-92.Developing cotyledons of Fhaseolus vulgaris L. were labeled for 30 min with pH] amino acids, homogenized, and the proteins fractionated on sodium dodecylsulfate (SDS) polyacrylamide gels. Fluorographs of these gels showed that the polypeptides of phaseolin, the major reserve protein ofF. vulgaris, were synthesized as precursors whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…We have studied the intracellular trafficking of phaseolin, the major vacuolar storage glycoprotein of common bean seeds. In developing bean cotyledons, phaseolin is transported to the protein storage vacuoles (PSV): upon arrival at the PSV, a short propeptide is proteolytically removed from phaseolin (Bollini et al 1982, D'Amico et al 1992). This trimming event occurs at the C-terminus and involves only four or five amino acids (Bollini et al 1982, Bollini and Vitale, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the intracellular trafficking of phaseolin, the major vacuolar storage glycoprotein of common bean seeds. In developing bean cotyledons, phaseolin is transported to the protein storage vacuoles (PSV): upon arrival at the PSV, a short propeptide is proteolytically removed from phaseolin (Bollini et al 1982, D'Amico et al 1992). This trimming event occurs at the C-terminus and involves only four or five amino acids (Bollini et al 1982, Bollini and Vitale, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo labeling studies have also shown the appearance of 58 to 62 kD polypeptides after short-period labeling of oat caryopses (4). RER is thought to be the site of synthesis for legume reserve proteins (2). Recent evidence indicates that pea legumin is synthesized on the RER and transported into protein bodies, where it is processed into smaller acidic and basic subunits (6).…”
mentioning
confidence: 99%
“…Reserve proteins are made on membrane-bound polysomes (4,11) and sequestered in the ER (2,5,7) prior to transport to the protein bodies (7). If lectins have a similar site of synthesis (4,13) and pathway of transport, the ER probably contains a pool of lectin molecules en route to the protein bodies.…”
mentioning
confidence: 99%